1975
DOI: 10.1172/jci108028
|View full text |Cite
|
Sign up to set email alerts
|

Human adipocyte cholesterol. Concentration, localization, synthesis, and turnover.

Abstract: A B S T R A C T By analysis of 124 specimens in 16 different patients, isolated human adipocyte cholesterol concentration is highly correlated with fat cell size but not with plasma cholesterol concentration. Less than 6% of total cholesterol is esterified; after subcellular fractionation, 88% of the cholesterol is recovered in the triglyceride-rich supernatant oil. This latter finding supports the observation that fat cell cholesterol is determined by triglyceride content, and hence by fat cell size.After int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
4

Year Published

1976
1976
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(62 citation statements)
references
References 14 publications
2
55
1
4
Order By: Relevance
“…Instead, the cholesterol secretion rate is increased and directly related to the extent of obesity. This high cholesterol output into bile agrees with the increased cholesterol turnover documented in obesity (43,44), the source of which presumably arises in the liver or intestine rather than from adipose tissue (45).…”
Section: Discussionsupporting
confidence: 82%
“…Instead, the cholesterol secretion rate is increased and directly related to the extent of obesity. This high cholesterol output into bile agrees with the increased cholesterol turnover documented in obesity (43,44), the source of which presumably arises in the liver or intestine rather than from adipose tissue (45).…”
Section: Discussionsupporting
confidence: 82%
“…Rather, it has been suggested that adipose tissue might be a sink for circulating cholesterol, which could help to buffer the high levels of circulating cholesterol frequently found in obese states. Because adipose tissue cholesterol content is strongly correlated with fat cell size in humans or rodents (23,25), we have proposed that intracellular cholesterol in adipocytes might act as a cell size-dependent intracellular signal, and might serve as a sensor for the level of intracellular triglyceride stores (28). In that view, the low ability of adipocytes for cholesterol efflux fits with cholesterol being a signaling molecule in fat cells, linked to the levels of energy stores.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to its well-known function in the managing of energy stores in the form of triacylglycerol, adipose tissue also contains the largest pool of cholesterol in the body. In fat tissue, cholesterol synthesis is extremely low (25), and most cholesterol is taken up from the circulation and is deposited in the free nonesterified form. In this regard, cholesterol storage in fat can be considered a "buffering" process, which might help to avoid hypercholesterolemia.…”
mentioning
confidence: 99%
“…The positive correlation between Ms and adiposity is consistent with the finding that adipose tissue cholesterol appears to be an important part of the most slowly turning over compartment, pool 3 (34). Schreibman and Dell have reported recently cholesterol turnover studies of 10-20 wk duration in which a threepool model was fit simultaneously to both plasma and adipocyte specific activity-time curves (34). In five of six subjects, the kinetics of adipose tissue cholesterol closely fit that of the slowly turning over pool 3.…”
Section: Turnover Of Plasma Cholesterol In Normal and Hyperlipidemic mentioning
confidence: 92%